Perlindungan Hak Anak Menurut Konvensi Hak Anak Tahun 1989 Ditengah Krisis Global Covid-19 - Oldrik Metekohy (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The rights of children who are deprived of their freedoms that occur in the midst of the global Covid-19 crisis that require legal attention and protection.Purposes of the Research: Knowing and analyzing about the legal protection of the rights of children who are deprived of their freedom in the midst of the global Covid-19 crisis according to the 1989 Convention on the Rights of the Child.Methods of the Research: This study uses a normative juridical method with the legal materials used in the study are primary, secondary and tertiary with the use of literature study techniques in the form of international legal regulations, scientific papers and literature.Results of the Research: The results of the research show that violations of children's rights in the midst of a pandemic are still common, both physically and mentally. There are still many violations of the 1989 Convention on the Rights of the Child.